Development and characterization of ceramic nanofiber membranes for dye removal from textile wastewater - Soylu Yerli, Nuray (Graduate School, 2024)
The development of industry and increasing of population day by day increase the demand for efficient management of water resources to protect both human health and the environment. Organic pollutants in water, particularly textile dyes, pose a significant threat to living organisms and human health due to their mutagenic and non-biodegradable nature. These dyes need to be removed from wastewater and treated before being released into the environment. Various physical, chemical and biological methods such as chemical coagulation, filtration, adsorption, flocculation, electrochemical precipitation and Fenton reaction are used to remove these pollutants from water. However, due to their structure, organic dyes are resistant to many treatment methods and some even cause secondary pollution. Moreover, these techniques can be costly and inefficient for color removal. In recent years, photocatalytic methods have come to the fore in purifying colored textile wastewater at the desired concentrations and converting it into the relatively safe materials, with advantages such as breaking down organic pollutants into harmless end products with sunlight, high mineralization efficiency, and low cost. Semiconductor based heterogeneous photocatalysis method with antibacterial applications for the degradation of both organic and inorganic pollutants is seen as a promising technology, especially in water and air purification. In photocatalytic process, an effective photocatalyst should absorb a photon with energy equal to or higher than its band gap. An electron moves from the valence band to the conduction band by this way, which results forming of an electron-hole pair. Among different semiconductor catalysts, TiO2 stands out due to its superior properties. TiO2, especially in the anatase phase, provides advantages due to its chemical and biological inertness, photochemical stability, low cost, non-toxicity and ease of production. However, the wide band gap energy of anatase TiO2 (3.2 eV) restricts its activation to UV irradiation, which constitutes only 4-5% of sunlight in terms of energy, limiting its effective use in industrial applications. In recent years, researchers have been focused on various structural modifications and doping methods to make TiO2 active under visible light. In these studies, it was aimed to decrease the rate of electron-hole recombination in the photocatalysis process, increasing the surface area and making maximum use of solar energy by doping TiO2 with different metals or metal oxides, non-metallic elements, lanthanide ions and/or their combinations etc. Additionally, stabilization of TiO2 nanoparticles is a very difficult and complex process. To be able to solve this problem, photocatalysts containing TiO2 coated on ceramic, glass and metal surfaces with using sol-gel method. However, in these applications, TiO2 is peeled off from the coated surface. In order to overcome this problem, TiO2 was directly incorporated into glass-ceramic systems. TiO2 nanofibers combined with different metal oxides, and lanthanide ions obtained by the combination of sol-gel and electrospinning methods have been attracted attention for photocatalytic applications due to their advantages such as high surface area/volume ratio, extraordinary length, regular-sized fiber diameters, and the possibility of being produced in various compositions. Within the scope of the thesis study, ceramic nanofibers containing multiple oxides based on TiO2 were synthesized by modified sol-gel without aging and drying steps, and electrospinning methods. Firstly, to determine the composition of the nanostructured materials to be obtained, solutions consisting of different oxide compositions were prepared, and nanofiber membranes were fabricated by the electrospinning method. In order to achieve the goal of obtaining nanofibers with homogeneous distribution, bead-free structure and low diameter by the electrospinning process, the effects of the electrospinning process parameters were investigated with the Box-Behnken experimental design method. At this stage, as a result of preliminary studies, a sol-gel solution was prepared with the precursors composed of 59TiO2-18.1SiO2-12.5CaO-9Al2O3-1.4CeO2 (in wt. %). As a result of the experimental design, the photocatalytic activity of the ceramic nanofiber was investigated with methylene blue (MB) under UV, and simulated sunlight irradiation. In the next part of the study, the TiO2 ratio in the nanofiber membrane content was increased, and zirconium (Zr+4), whose ionic diameter is similar to titanium (Ti+4), was added to improve both the photocatalytic, and structural properties of the obtained nanomaterials. TiO2-based ceramic nanofiber membranes consisted of 65TiO2-20SiO2-5Al2O3-5ZrO2-3CaO-2CeO2 (in wt. %) were synthesized by combining sol-gel and electrospinning processes. In order to investigate the thermal treatment effect, the obtained nanofiber membranes were calcined at different temperatures ranging from 550⁰C to 850⁰C. Different characterization methods such as XRD, SEM, FT-IR, XPS, and HR-TEM were conducted on the obtained membranes to investigate the structural and morphological properties. The BET surface area of the nanofiber membranes was very high (46.6 – 149.2 m2/g), and decreased with increasing calcination temperature as expected. Photocatalytic activity investigations were determined using with 10-20 ppm MB under UV, and simulated sunlight irradiation. High degradation performances were achieved with the calcination temperature of 650⁰C and 750⁰C because of the high specific surface area, and anatase structure of the nanofiber membranes. Moreover, the ceramic membranes showed remarkable antibacterial activity against Escherichia coli as a Gram-negative bacteria and Staphylococcus aureus as a Gram-positive bacteria. In the next part of the study, nanofiber membranes with the composition of 65TiO2-15SiO2-10B2O3-4Al2O3-3ZrO2-3CaO (in wt.%), which contain high levels of boron and silicon, and relatively lower levels of zirconium, aluminum, and calcium, were obtained as a result of preliminary experiments. In this sample, which can be easily fabricated by applying low voltage with electrospinning and has superior nanofiber properties, the effect of high boron content on photocatalytic, and antibacterial applications was investigated. The obtained nanofibers were calcined in the temperature range of 550°C-850°C, and their BET surface areas were found to be 24.49 - 147.94 m²/g. The highest MB removal (93.5%) was achieved with ceramic nanofibers calcined at 750°C, whose anatase crystalline structure was confirmed by XRD, and HR-TEM analysis. Additionally, promising antibacterial activity results were obtained against different microorganisms (Escherichia coli, Pseudomonas aeruginesa, and methicilin-resistant Staphylococcus aureus) due to the high amount of boron, and other dopants added to the TiO2 ceramic matrix. In the last part of the thesis, the design of a photocatalytic reactor cell that can be a model for the removal of pollutants from wastewater, and its production with a 3D printer were realized. This designed cell offers an engineering standard that can enable industrial design opportunities for materials with water purification properties via photocatalytic activity. Also, it improves research activities by providing comprehensive photocatalytic activity characterization. An experimental set-up was established, where wastewater containing dye was continuously entering the cell with a photocatalyst placed inside, and decolorized water was continuously leaving from the system with the help of a peristaltic pump that allows operation at low flow rates. The effects of different photocatalyst mass (20-60 mg), and flow rates (0.6-2 ml/min) on photocatalytic activity under a continuous flow were investigated. As a result of the experiments carried out within the scope of the thesis study, it was concluded that the obtained multi-doped TiO2 ceramic nanofibers with different compositions can be promising candidates that can provide high efficiency in both antibacterial and photocatalytic applications for dye removal from textile wastewater. In addition, the proof of the effectiveness of samples in a continuous system using a photocatalytic reactor cell produced with a 3D printer for the first time laid the foundation for dye removal from wastewater on an industrial scale.
Tekstil atıksularından boya giderimi için seramik nanofiber membranların geliştirilmesi ve karakterizasyonu
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2024
Keywords: wastewater; atık su; textile wastewater; tekstil atıksuları; ceramic nanofiber; seramik nanofiber; membranes; membranlar